СОВРЕМЕННЫЙ СОСТАВ ИХТИОФАУНЫ Р. ШЕЛЕК B ГОРНОЙ И ПРЕДГОРНОЙ ЗОНАХ (ҚазҰУ хабаршысы. Экология сериясы, 2016)
The data on current composition of the Shеlek River ichthyofauna as well as its vertical distribution was provided. Due to natural- geographical reasons and low anthropogenic load in this river, the favorable conditions for existence and reproduction of native fish species like scaleless osman Diptychus dybowskii, Thibet stone loach Triplophysa stoliczkai, plain stone loach T.labiata as well as alien Kamchatka steelhead Paraslmo mykiss (Salmo gairdnerii). The data on density offish distribution and their brief biological characteristics were presented.